USING TIKTOK ENGLISH ACTING CHALLENGE VIDEOS TO IMPROVE STUDENTS’ SPEAKING ABILITY AT SMA NEGERI 2 TONDANO - Jutelia Sala; Ignatius J. Tuerah; Jennie Posumah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this research is to find out if the Tik-Tok English Acting Challenge videos may help students to improve their speaking ability especially their pronunciation.This is a quantitative study using pre-test and post-test design through an oral test.The subjects of this study were 20 students from SMA Negeri 2 Tondano's class 10 A. Based on the data obtained,the highest Pre-test score is 8 and the lowest is 4, while the highest Post-test score is 10 and the lowest is 6 with the mean score in the Pre-test is 4.7 and the mean score in the Post-test is 8.2. Significant improvements can be noted in this data, and it can be concluded that the feature of Tiktok English Acting Challenge videos successfull in enchancing and upgrading students' Speaking Ability